The Main Causes of English for Occupational Purposes Students (EOP) Speaking Anxiety - Rifki Irawan (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2023)
This paper aimed at investigating the main causes of English for Occupational Purposes (EOP) students’ speaking anxiety. The study involved a total of eight students from two different classes with varying levels of English proficiency. It focused on a case study conducted in an Indonesian company and utilized three types of research instruments, namely classroom observation FLCAS (Foreign Language Classroom Anxiety Scale) questionnaires by Horwitz (1986) and semi-structured interviews. The study revealed that experiences in communicating, the kind of students’ occupation and Foreign Language Acquisition (FLA) are the main causes of EOP students’ speaking anxiety.